Computational Fluid Dynamics Analysis of Stove Systems for Cooking and Drying of Muga Silk - Anal Ranjan Sengupta; R. Gupta; A. Biswas (Emerging Science Journal, 2019)
In India, Silk industry plays an important part in textile industry. Muga silk, the golden yellow silk is quite unique to Assam, North-east India where its production is regarded as an important tool for economic development. But, outdated manufacturing technology is followed during the silk production in Assam. The existing cooking process of silk cocoons consists of boiling of silk cocoons in a stainless steel vessel along with water and soda in an open fireplace which is highly energy inefficient. Therefore, two modified systems have been designed; one having cylindrical boiling chamber (vessel) and the other having spherical boiling chamber (vessel). Both the chambers are having a cocoon heating chamber associated with them for cooking and drying of silk cocoons simultaneously. These designs are further classified into two types of designs based on channel and nozzle type combustion chambers. Therefore, the main objective of this paper is to improve the existing designs to maximize the utilization of heat carried by the combustion gases. These modified systems are analysed by using Computational Fluid Dynamics (CFD) selecting standard k–є model. From the analysis, it is seen that these new systems having nozzle type combustion chambers are more efficient than the systems having cylindrical combustion chambers and if these systems are used in silk production, it will be very beneficial for the silk industry as well as for our society.